Spatial analysis of cerebral palsy in children and adolescents and its association with health vulnerability - Marcus Valerius Peixoto; Andrezza Marques Duque; Allan Dantas Santos; Shirley Verônica Almeida Melo Lima; Társilla Pereira Gonçalves; Ana Paula de Souza Novais; Susana de Carvalho; Silvia Maria Voci; Karina Conceicao Gomes Machado de Araujo; Marco Antônio Prado Nunes (Geospatial Health, 2020)
Cerebral Palsy (CP) is commonly associated with low socioeconomic status. Use of spatial statistics and a Geographic Information Systems (GIS) are scarce and may contribute to the understanding of CP in a social context. To that end a spatial analysis of CP in children and adolescents was performed to analyze the association of CP with levels of vulnerability in a city (Aracaju, Sergipe) in north-eastern Brazil. In addition, an ecological study was conducted with data obtained from a populationbased survey and secondary data. Exploratory spatial data analysis and linear regression were used. A total of 288 CP cases were identified, with a prevalence of 1.65/1,000 and differences among city neighbourhoods ranging from 0-4/1,000. The mean age of cases studied was 9 years 1 month, with a standard deviation of 5 years 2 months. Most study subjects with cerebral palsy (163) were male (56.4%). The distribution of CP in the study population was not homogeneous throughout the territory. Some areas had clusters, with more cases associated with areas of high vulnerability. Spatial data analysis using GIS was useful to gain an epidemiological understanding of CP distribution that can guide decisionmaking with respect to production, distribution, and regulation of health goods as well as services at the local level.